Tutorial on Location-Based Social Networks - Zheng, Yu (proceeding of the 21st International conference on World Wide Web, 2012)
This is a tutorial on location-based social networks (LBSNs), introducing the concept, unique features, and research philosophy of LBSNs and the representative research into LBSNs. The homepage of LBSN is http://research.microsoft.com/en-us/projects/lbsn/default.aspx.